Different forms of swimmers' final weeks pre-competition preparation - KAMIL SOKOLOWSKI; MAREK STRZALA; ARKADIUSZ STANULA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
The pre-competition training phase is a period that precedes the main competition. Combined training phases of overload training (OT) and taper (TP) create the most popular pattern of final form preparation among the swimmers despite the methodology difficulties faced by coaches. In the IPC, the duration and training load were strictly set. The main purpose of training in the IPC is to cause a substantial supercompensation effect by the high volume and capacity of the training. However, high volume and intensity fluctuations typical of the IPC may cause performance regression due to overtraining and exhaustion. The main aim of the taper phase (TP) is to provide recovery and develop peak racing capability for a particular event. This process relies on gradual reduction of training overload (mainly volume) in order to achieve the peak racing ability, after the planned, already achieved high level of swimming performance and efficiency. The duration of the TP and the form of load reduction are crucial factors affecting improvements in the swimmer's competition times. The TP strategy was identified as the safest and the most beneficial one. This paper aims at providing characterization of training procedures used in IPC and TP, together with a presentation of the physiological mechanism exploited here and a possible performance improvement.